2006
DOI: 10.1577/t05-122.1
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile Pallid Sturgeon are Piscivorous: A Call for Conserving Native Cyprinids

Abstract: We examined the diets of age-6 and age-7

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
94
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(100 citation statements)
references
References 19 publications
3
94
3
Order By: Relevance
“…Both the Upper Basin Pallid Sturgeon Work Group (UBPSWG 2002) and technical experts from state and federal agencies, universities, and private organizations (Quist et al 2004) identified food habits of age-1 and older pallid sturgeon as a high priority research item. Gerrity et al (2006) evaluated the food habits of age-6 and age-7 juvenile pallid sturgeon in a relatively unaltered stretch of the Missouri River above Fort Peck Reservoir, Montana and determined that native benthic cyprinids were important in their diet. Thus, the objectives of this study were to 1) assess food habits of juvenile pallid sturgeon in the highly altered Missouri River between two mainstem dams and 2) compare seasonal food habits and diet overlap between juvenile pallid sturgeon and shovelnose sturgeon.…”
Section: Introductionmentioning
confidence: 99%
“…Both the Upper Basin Pallid Sturgeon Work Group (UBPSWG 2002) and technical experts from state and federal agencies, universities, and private organizations (Quist et al 2004) identified food habits of age-1 and older pallid sturgeon as a high priority research item. Gerrity et al (2006) evaluated the food habits of age-6 and age-7 juvenile pallid sturgeon in a relatively unaltered stretch of the Missouri River above Fort Peck Reservoir, Montana and determined that native benthic cyprinids were important in their diet. Thus, the objectives of this study were to 1) assess food habits of juvenile pallid sturgeon in the highly altered Missouri River between two mainstem dams and 2) compare seasonal food habits and diet overlap between juvenile pallid sturgeon and shovelnose sturgeon.…”
Section: Introductionmentioning
confidence: 99%
“…P-M and M-T). The diets of these two species have low similarity niche (Gerrity et al 2006). For the most part, only reproductively ready pallid sturgeon are achieving a Kn greater than 0.90, which is the effect of gonadal development, while the current mean population Kn is approaching the lower end of that recommendation.…”
Section: Discussionmentioning
confidence: 98%
“…Comm. ), (4) food availability by calculating CPUE from the NGPC's PSPA Program's standardized sampling efforts for (a) annual otter trawl catch rates for sturgeon and sicklefin chubs which were described as primary prey items by Gerrity et al (2006), (b) annual otter trawl catch rates for a suite of species documented by Winders et al (2014), and (c) annual mini-fyke net catch rates for all small bodied fish. Since the majority of pallid sturgeons are collected in March and April, before the independent variables were measured, independent variables were set forward one year to adjust to the observed conditions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The shoal chub (Macrhybopsis hyostoma) serves as key food chain species for the endangered pallid sturgeon (Scaphirhynchus albus) (Gerrity et al 2006;Herman et al 2008) and has been experiencing significant population declines throughout their ranges, which may be attributable to anthropogenic disturbances (Hesse 1994;Steffensen et al 2014). Previous molecular studies were unable to resolve the phylogeny of Macrhybopsis chubs with singular mitochondrial markers, making identifying populations that are susceptible to anthropogenic disturbances difficult (Nagle & Simons 2012).…”
mentioning
confidence: 99%